2020
DOI: 10.1155/2020/3436940
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Enzyme Inhibition Potentials, and Phytochemical Profiling of Premna serratifolia L. Leaf Extracts

Abstract: Premna serratifolia, commonly known as Arogo in Tentena-Sulawesi, is a popular vegetable. As a promising herbal tea and food ingredient, further investigation is required to find the best knowledge for medicinal use of P. serratifolia leaves. This research investigated the antioxidant activity of the ethanol (EEPS) and water (WEPS) extracts of P. serratifolia leaves, based on their scavenging activities on DPPH radicals and their reducing capacities (CuPRAC, total antioxidant/phosphomolybdenum, and ferric thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
15
1
1
Order By: Relevance
“…Determination of xanthine oxidase inhibition activity was conducted following a reported method. 12 Xanthine was used as a substrate and allopurinol was used as a reference inhibitor. Sample of different concentrations (100 µL) was mixed with xanthine oxidase (0.2 U/mL, 100 µL) and phosphate buffer (50 mM pH 7.4, 400 µL).…”
Section: Determination Of Xanthine Oxidase Inhibition Activitymentioning
confidence: 99%
“…Determination of xanthine oxidase inhibition activity was conducted following a reported method. 12 Xanthine was used as a substrate and allopurinol was used as a reference inhibitor. Sample of different concentrations (100 µL) was mixed with xanthine oxidase (0.2 U/mL, 100 µL) and phosphate buffer (50 mM pH 7.4, 400 µL).…”
Section: Determination Of Xanthine Oxidase Inhibition Activitymentioning
confidence: 99%
“…herbal formulation/ iridoid prevent age-related disorders, supersede the ageing process [27] Many bioactive compounds in PS extracts, such as forsythoside A and B, lavandulifolioside, diosmin, nobilin D, campneoside I, isoactoside. scoriside E [2], terpenoid, oleanolic acid, stigmasterol have important activities that are associated with various diseases.…”
Section: Herbal Formulation/ Iridoidmentioning
confidence: 99%
“…Simamora et al, have reported proteinase, lipase. Water and ethanol extract of PS can inhibit several key enzymes in health and diseases, namely α-glucosidase, α-amylase, xanthine oxidase, and protease [2]. Further researches are needed for the inflammatory and neurological enzymes, tyrosinase and lipase.…”
Section: Inhibitory Activities Against Enzymesmentioning
confidence: 99%
See 2 more Smart Citations